An Overview of Methods for Blast Load Testing and Devices for Pressure Measurement - H. Draganić; D. Varevac; S. Lukić (Advances in Civil Engineering)
A brief review of experimental methods for testing blast effects on structures is presented. Methods are classified in four groups: field tests, shock tubes, pendulum systems, and new techniques (blast simulator). Description of each method is given together with overall specification of possible instruments used in each test. In today’s modern era of computers which are becoming powerful tool implemented in all aspects of life and also scientific research, comparison of experimental and numerical techniques is also given. Comparison of data obtained from different experimental methods show that careful planning and execution leads to reliable results in terms of pressure, impulse, stress, and damage quantification.